2007
DOI: 10.1007/s12262-007-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

The Limberg flap for cutaneous defects — a two year experience

Abstract: Aim To evaluate the Limberg or rhomboid fl ap done during the past 2 years with regard to applicability, reliability and complications.Methods All Limberg fl aps done were reviewed by inspecting case records and directly following up patients. The indications, suitability, post-operative course and complications were noted.Results Eleven Limberg fl aps were done during this period. Seven patients underwent the procedure for cutaneous malignancies. Rest for various benign lesions. All the fl aps survived. One p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…On the contrary, Mathew et al [ 15 ] reported the execution of Limberg flaps in 11 patients, 9 males and 2 females, with age ranging from 45 to 76 years. The mean age was higher, as most of the patients had cutaneous malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Mathew et al [ 15 ] reported the execution of Limberg flaps in 11 patients, 9 males and 2 females, with age ranging from 45 to 76 years. The mean age was higher, as most of the patients had cutaneous malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The Limberg Rhomboid flap has been used successfully in repairing the cutaneous defects due to malignancy, bed sores, pilonidal sinus and traumatic ulcers as evidenced by past studies. [4][5][6][7][8] In our study as well we have used rhomboid flap for similar cases. We have used rhomboid flap to cover the cutaneous defect by creating a similar shaped flap of equal size by mobilizing the lax skin of same texture and skin color.…”
Section: Discussionmentioning
confidence: 99%
“…2 The pedicle of the flap maintains subpapillary and sub-dermal vascular plexuses to provide superior results when compared to skin grafts of similar size and location. 12,13 A reduction in tension on the flap decreases the likelihood of necrosis of the donor tissue. 14 The design is a parallelogram with two angles of 120 degrees and two angles of 60 degrees.…”
Section: Case Seriesmentioning
confidence: 99%